1985
DOI: 10.1104/pp.79.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome Control of Levels of mRNA Complementary to Plastid and Nuclear Genes of Maize

Abstract: The involvement of phytochrome in the control of the levels of RNA tranbed from maize plastid and nuclar genes was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 24 publications
7
51
0
Order By: Relevance
“…This light regulation is attributable in part to the phytochrome signal transduction pathway because the levels of Ppc and RbcS2 are reduced in the phytochrome-deficient elm1 mutant under R and FR. Previous studies have demonstrated a role for R in inducing cell-specific expression of Ppc (Langdale et al, 1988a;Thomas et al, 1990;Schaffner and Sheen, 1992) and RbcS (Zhu et al, 1985;Purcell et al, 1995) after a shift from D to light growth. Here, we demonstrate the involvement of R, B, and FR light on maintaining the levels of Ppc and RbcS2 in fully differentiated C4 photosynthetic tissues.…”
Section: Influence Of Light Quality On Photosynthetic Differentiationmentioning
confidence: 99%
“…This light regulation is attributable in part to the phytochrome signal transduction pathway because the levels of Ppc and RbcS2 are reduced in the phytochrome-deficient elm1 mutant under R and FR. Previous studies have demonstrated a role for R in inducing cell-specific expression of Ppc (Langdale et al, 1988a;Thomas et al, 1990;Schaffner and Sheen, 1992) and RbcS (Zhu et al, 1985;Purcell et al, 1995) after a shift from D to light growth. Here, we demonstrate the involvement of R, B, and FR light on maintaining the levels of Ppc and RbcS2 in fully differentiated C4 photosynthetic tissues.…”
Section: Influence Of Light Quality On Photosynthetic Differentiationmentioning
confidence: 99%
“…In etiolated monocot and dicot seedlings phyA is the predominant phytochrome species (Quail, 1994;Smith, 1995) and it has been extensively shown that red and far-red light are the primary signals stimulating chloroplast transcription and mRNA accumulation (Bottomley, 1970;Link, 1982;Thompson et al, 1983;Zhu et al, 1985). In etiolated pea the activation of chloroplast transcription is a high-irradiance response to far-red light mediated by phyA (Dubell and Mullet, 1995).…”
Section: Developmental Change In Action Spectrum For Chloroplast Tranmentioning
confidence: 99%
“…Previous research on the role of phytochrome in chloroplast gene expression depended on varying light quality and fluence treatments of wild-type plants, particularly, seedlings (Bottomley, 1970;Link, 1982;Thompson et al, 1983;Zhu et al, 1985;Dubell and Mullet, 1995;Christopher, 1996). To our knowledge no studies have used the two systems described here to examine the photobiology of chloroplast transcription and to measure chloroplast transcription directly in a phytochrome mutant.…”
Section: Blue Light/uv-a Activate Chloroplast Transcription In Maturementioning
confidence: 99%
See 2 more Smart Citations